(untitled) (World Bulletin of Social Sciences, 2022)
This article shows the easiest and relatively inexpensive way to adjust the speed of rotation of induction motors - the ability to adjust the speed using two-speed asynchronous motors with a variable number of poles. Comparison and analysis of the main energy characteristics of two-speed single-winding and double winding asynchronous motors is carried out. Based on the data obtained, two-speed motors with a variable number of poles are proposed as an asynchronous motor as part of an electric drive.